2019
DOI: 10.1042/ns20180205
|View full text |Cite
|
Sign up to set email alerts
|

5-HT2A receptor loss does not alter acute fluoxetine-induced anxiety and exhibit sex-dependent regulation of cortical immediate early gene expression

Abstract: Background: Acute treatment with the selective serotonin reuptake inhibitor (SSRI), fluoxetine (Flx), induces anxiety-like behavioral effects. The serotonin2A receptor (5-HT2A) is implicated in the modulation of anxiety-like behavior, however its contribution to the anxiogenic effects of acute Flx remains unclear. Here, we examined the role of the 5-HT2A receptor in the effects of acute Flx on anxiety-like behavior, serum corticosterone levels, neural activation and immediate early gene (IEG) expression in str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…As expected, male KO showed a decrease in the 5-HT 2A R gene compared to vehicle WT (Tukey pot-hoc, p < 0.05), like in a previous report using this knockout mouse model [39]. 5-HT 2A R showed statistical differences for all factors, including treatment (F (2,47) = 7.40, p < 0.01, N = 7-10), genotype (F (1,47) = 47.95, p < 0.0001, N = 7-10), and interaction (F (2,47) = 8.27, p < 0.001, N = 7-10).…”
Section: -Ht 2a Receptor Deficiency Alters the Gene Expression Profil...supporting
confidence: 87%
“…As expected, male KO showed a decrease in the 5-HT 2A R gene compared to vehicle WT (Tukey pot-hoc, p < 0.05), like in a previous report using this knockout mouse model [39]. 5-HT 2A R showed statistical differences for all factors, including treatment (F (2,47) = 7.40, p < 0.01, N = 7-10), genotype (F (1,47) = 47.95, p < 0.0001, N = 7-10), and interaction (F (2,47) = 8.27, p < 0.001, N = 7-10).…”
Section: -Ht 2a Receptor Deficiency Alters the Gene Expression Profil...supporting
confidence: 87%
“…The mechanisms of the increased suicidal risk of antidepressants among adolescents were not quite clear; however, some studies in animal models have found that treatment with SSRIs could exert potent anxiogenic behavioral effects, in particular during the acute phase of treatment ( 57 59 ). The inhibitory circuit of corticotropin-releasing factor neurons in the bed nucleus of the stria terminalis may contribute to the aversive behavior following acute exposure to SSRIs ( 58 ).…”
Section: Discussionmentioning
confidence: 99%